2022
DOI: 10.1016/j.sopen.2021.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Low free testosterone is associated with increased mortality in frail surgical patients

Abstract: Background Preoperative frailty has been associated with adverse postoperative outcomes. Additionally, low testosterone has been associated with physical frailty and cognitive decline. However, the impact of simultaneous frailty and low testosterone on surgical outcomes is understudied. Methods Preoperative frailty status and testosterone levels were obtained in patients undergoing a diverse range of surgical procedures. Preoperative frailty was evaluated independently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous investigations demonstrated the benefits of preoperative testosterone administration, even at higher than physiological levels, to minimize postoperative adverse outcomes and improve recovery following major surgeries ( 26 , 27 ). Studies have also shown that low free testosterone concentration is associated with increased mortality rates after major surgeries ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations demonstrated the benefits of preoperative testosterone administration, even at higher than physiological levels, to minimize postoperative adverse outcomes and improve recovery following major surgeries ( 26 , 27 ). Studies have also shown that low free testosterone concentration is associated with increased mortality rates after major surgeries ( 28 ).…”
Section: Introductionmentioning
confidence: 99%